RNAi-Based Therapy: Prospect as Cancer Treatment - Soentoro, Samuel E; Timothy, Michael; Jo, Juandy (Medicinus, 2024)
Cancer is one of the deadliest form of diseases in humans, with the annual deaths ranging in the millions. Conventional treatments including chemotherapy, radiotherapy, or surgery has their limitations, including common off-target and non-specific effects. Ribonucleic acid interference (RNAi) offers a new strategy for treating cancer by silencing specific genes to prevent gene expression. This review highlights the application of RNAi-based approach in targeting cancer, discusses its potential advantages and limitations, summarizes the existing clinical trials and provides a greater understanding of RNAi-based therapy in cancer.